2017
DOI: 10.3390/educsci7040090
|View full text |Cite
|
Sign up to set email alerts
|

Academic Advising Systems: A Systematic Literature Review of Empirical Evidence

Abstract: This paper aims to provide the reader with a comprehensive background for understanding current knowledge on Academic Advising Systems (AAS) and its impact on learning. It constitutes an overview of empirical evidence behind key objectives of the potential adoption of AAS in generic educational strategic planning. The researchers examined the literature on experimental case studies conducted in the domain during the past ten years (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017). Search terms ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…These processes and procedures are multifaceted (Tam, 2010) and raise constant challenges to management and administration at different levels (Ibrahim, 2015) (Iatrellis, Kameas, & Fitsilis, 2019). From student's perspective, educational processes, especially those belonging to the higher educational sector, are acknowledged as complex and characterized by the plethora of academic choices, the local constraints, the student's needs and the dynamic nature of the defining personalized educational goals (Vizcarro & Vos, 2002) (Iatrellis, Kameas, & Fitsilis, 2017). Of course, process complexity is not unique in education.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes and procedures are multifaceted (Tam, 2010) and raise constant challenges to management and administration at different levels (Ibrahim, 2015) (Iatrellis, Kameas, & Fitsilis, 2019). From student's perspective, educational processes, especially those belonging to the higher educational sector, are acknowledged as complex and characterized by the plethora of academic choices, the local constraints, the student's needs and the dynamic nature of the defining personalized educational goals (Vizcarro & Vos, 2002) (Iatrellis, Kameas, & Fitsilis, 2017). Of course, process complexity is not unique in education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Calculate β that means risk factor for each Aij with (6). 6) where t denotes the set of all actives and the number of actives in a project network, respectively. 6.…”
Section: Ns(j) = {K | Ajk ∈ S(j) K ∈ N} F(j)mentioning
confidence: 99%
“…The idea of [5] assists the Researcher on assessment of the current academic advising. It helps the proponent to visualize the flow of the current advising system and supports for helping analyze how to solve the problem.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Many universities have an advising system or recommendation system, which employ guideline counsellors, people who are tasked with helping students making their choice, including developmental advising, helping them schedule the most suitable programs, assisting in career development, helping them in timely completion of their studies and student"s academic performance (Iatrellis, Kameas, &Fitsilis, 2017). Daramola, et al (2014) reported that some advisors hold too many students or are overloaded on advising students, in which they are supposed to accommodate a good outcome in terms of understanding, planning and applying strategies for academic success.…”
Section: Introductionmentioning
confidence: 99%